2011
DOI: 10.1016/j.ydbio.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Conditional disruption of mouse Klf5 results in defective eyelids with malformed meibomian glands, abnormal cornea and loss of conjunctival goblet cells

Abstract: Members of the Krüppel-like family of transcription factors regulate diverse developmental processes in various organs. Previously, we have demonstrated the role of Klf4 in the mouse ocular surface. Herein, we determined the role of the structurally related Klf5, using Klf5-conditional null (Klf5CN) mice derived by mating Klf5-LoxP and Le-Cre mice. Klf5 mRNA was detected as early as embryonic day 12 (E12) in the cornea, conjunctiva and eyelids, wherein its expression increased during development. Though the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 54 publications
2
63
1
Order By: Relevance
“…It has previously been reported that the conditional knockout of Krüppel-like factors 4 or 5 (Klf4 or Klf5) in the ocular surface epithelia with Le-Cre driver also caused a failure of goblet cell formation (Swamynathan et al, 2007;Kenchegowda et al, 2011). This result prompted us to test whether dnMaml1 could impact the expression of Klf4 and Klf5.…”
Section: Dnmaml1 Downregulated Expression Of Krüppel-like Factors Andmentioning
confidence: 99%
“…It has previously been reported that the conditional knockout of Krüppel-like factors 4 or 5 (Klf4 or Klf5) in the ocular surface epithelia with Le-Cre driver also caused a failure of goblet cell formation (Swamynathan et al, 2007;Kenchegowda et al, 2011). This result prompted us to test whether dnMaml1 could impact the expression of Klf4 and Klf5.…”
Section: Dnmaml1 Downregulated Expression Of Krüppel-like Factors Andmentioning
confidence: 99%
“…Although the role of Spdef in goblet cell differentiation is consistent between the lung, the intestine and the conjunctiva, transcriptional control of Spdef remains unclear, especially in the conjunctiva. Conditional deletion of Klf4 (Swamynathan et al, 2007;Gupta et al, 2011) or Klf5 (Kenchegowda et al, 2011), which are structurally related and expressed in the ocular surface epithelium, results in a loss of conjunctival goblet cells and reduced Spdef mRNA expression Marko et al, 2013). Gene expression analysis of Klf4-deficient mice yielded Spdef, but not elements of the TGFβ signaling pathway, as direct targets of KLF4 in the conjunctiva .…”
Section: Tgfβ Is a Novel Regulator Of Spdefmentioning
confidence: 99%
“…Although the precise regulatory networks governing goblet cell differentiation in the conjunctiva are unknown, conjunctival phenotypes in murine models have identified Krüppel-like family 4 (KLF4) (Swamynathan et al, 2007;Gupta et al, 2011) and 5 (KLF5) (Kenchegowda et al, 2011), SAM pointed domaincontaining ETS transcription factor (SPDEF) (Marko et al, 2013) and the Notch signaling pathway as essential factors required for goblet cell differentiation in the mouse conjunctiva, as deletion of these genes, or inhibition of Notch signaling, results in conjunctiva that lack goblet cells. SPDEF plays a crucial role in goblet cell differentiation in multiple organs, including the lung (Park et al, 2007), the intestine Noah et al, 2010) and the conjunctiva (Marko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Foxc1 mediates the BMP signaling required for lacrimal gland development (Mattiske et al, 2006). Klf5 conditional null lacrimal glands showed a disrupted acinar organization (Kenchegowda et al, 2011) and Six1 −/− fetuses displayed small lacrimal glands (Laclef et al, 2003). However, little is known about the mechanisms required to initiate lacrimal gland formation by FGF signaling.…”
Section: Introductionmentioning
confidence: 99%